Role of Transient Receptor Potential Canonical Channels in Heart Physiology and Pathophysiology - Wen, Hairuo; Gwathmey, Judith K.; Xie, Lai-Hua (Frontiers in Cardiovascular Medicine, 2020)
Transient receptor potential canonical (TRPC) channels are involved in the regulation of cardiac function under pathophysiological conditions and are closely associated with the pathogenesis of cardiac hypertrophy, arrhythmias and myocardial infarction. Understanding the molecular mechanisms and the regulatory pathway/locus of TRPC channels in related heart diseases will provide potential new concepts for designing novel drugs targeting TRPC channels. We will present the properties and regulation of TRPC channels as well as their roles in the development of various forms of heart disease. This article provides a brief review on the role of TRPC channels in the regulation of myocardial function as well as how TRPC channels may serve as a therapeutic target in heart failure and cardiac arrhythmias including atrial fibrillation.